Long-term employment outcomes following moderate to severe traumatic brain injury: a systematic review and meta-analysis. (6th December 2019) - Gormley, Mirinda; Devanaboyina, Monika; Andelic, Nada; Røe, Cecilie; Seel, Ronald T.; Lu, Juan
ABSTRACT: Background : Returning to employment following moderate to severe traumatic brain injury (msTBI) is critical for a survivor's well-being, yet currently there are no systematic reviews that comprehensively describe employment outcomes following msTBI. The objective of this study was to systematically synthesize literature on employment outcomes following msTBI. Methods : Original studies published through April 2018 on MEDLINE/PubMed, PsychINFO, and CINAHL were eligible if the objective was to investigate employment outcomes following msTBI; outcome was measured ≥1 year; participants were ≥15; and size was ≥60. Post-injury employment prevalence and return to pre-injury level of work were summarized through meta-analysis. Results : Of 38 eligible studies, post-injury employment prevalence was most often reported (n = 35), followed by job stability (n = 6), and return to pre-injury level of work (n = 4). Overall post-injury employment prevalence was 42.2%; whereas the return-to-previous-work prevalence was 33.0%. Post-injury employment prevalence appeared to increase over time, from 34.9% at 1 year to 42.1% up to 5 years and 49.9% beyond 5 years. Conclusion : Nearly half of individuals with msTBI were employed post-injury, yet only a third returned to pre-injury level of work. Future researchers are recommended to standardize employment outcome measures to enable better comparison of outcomes across studies.